The Accomplishment and Future Study of Disability Identity Research in the Japanese Context: A Cross-Section of Psychology and Disability Studies - Tagaki, Masakuni (International Review of Theoretical Psychologies, 2026)
This study highlights the accomplishments of previous research on disability identity in the Japanese context. Disability identity is the belief that people with disabilities view disability as a positive and essential aspect of their sense of belonging to the disability community. Value-change theory in rehabilitation psychology implies the current disability identity, suggesting that people with disabilities have favorable attitudes toward themselves. However, this theory overlooks the uniqueness of their impairments. Disability identity emphasizes that disability has personal, collective, and political implications. Disability culture (e.g., “deaf” and anti-eugenic discourse) and disability policy encourage people with disabilities to narrate their disability-related experiences for themselves and the public. The lack of concrete regulations in Japan’s Disability Discrimination Act enables them to create diverse narratives. Their involvement in disability-related activities changes depending on their social and political contexts. Online platforms can serve as venues where users can share their experiences. In future, the generativity concept can contribute to understanding how disability identity is shaped across generations, while respecting differences among generations in their sense of belonging to the disability community. Finally, disability identity should not be overemphasized, as it may risk negating other important aspects of the person.